Dexmedetomidine for the management of postictal agitation after electroconvulsive therapy with S-ketamine anesthesia - Aksay, Suna Su; Remennik, Dmitry; Thiel, Manfred; Sartorius, Alexander; Janke, Christoph (Neuropsychiatric disease and treatment, 2017)
Dexmedetomidine for the management of postictal agitation after electroconvulsive therapy with S-ketamine anesthesia Suna Su Aksay,1 Jan Malte Bumb,2 Dmitry Remennik,3 Manfred Thiel,3 Laura Kranaster,1 Alexander Sartorius,1 Christoph Janke3 1Department of Psychiatry and Psychotherapy, Central Institute of Mental Health (CIMH), Medical Faculty Mannheim, University of Heidelberg, 2Department of Addictive Behavior and Addiction Medicine,Central Institute of Mental Health (CIMH), Medical Faculty Mannheim, University of Heidelberg, 3Department of Anesthesiology and Critical Care Medicine, Medical Faculty Mannheim, Heidelberg University, Germany Objectives: Postictal agitation (PIA) represents one of the most common complications during a modified electroconvulsive therapy (ECT) course. Its clinical management can be challenging especially in cases with poor response to benzodiazepines. Dexmedetomidine, a highly selective alpha-2 adrenoceptor agonist acting predominantly in the locus coeruleus, exerts sedative effects without causing relevant respiratory depression. To the best of our knowledge, this is the first study that aimed to assess the impact of dexmedetomidine use with S-ketamine anesthesia on PIA reduction in ECT.Patients and methods: We retrospectively analyzed 7 patients who underwent 178 ECT sessions with S-ketamine anesthesia between June 2011 and July 2015 at the Central Institute of Mental Health Mannheim. In 101 sessions, the patients received dexmedetomidine in combination with S-ketamine anesthesia. The decision for dexmedetomidine use was based on individual clinical presentation (patients with positive PIA history). A multivariate repeated measurement logistic regression analysis was conducted to investigate the effect of dexmedetomidine use on the occurrence of PIA. We hypothesized that the use of dexmedetomidine reduced the incidence of PIA also in combination with S-ketamine anesthesia.Results: The prevalence of PIA in ECT sessions with dexmedetomidine administration was lower (mean per patient, 34% vs 62%). In the multivariate logistic regression analysis, the use of dexmedetomidine predicted the non-occurrence of PIA in a highly significant manner (P=0.001, z=−3.83, odds ratio =0.011–0.303).Conclusion: Adjunctive use of dexmedetomidine to S-ketamine anesthesia in ECT seems to be a promising tool for the management of intractable PIA syndrome. Keywords: ECT, PIA, depression